La promenade dans les jardins de Versailles : analyse d’une expérience spatiale - Catherine Szanto (Projets de Paysage)
In order to appreciate a garden, the visitor must explore it. Thus, the garden must be a constant invitation, a succession of proposals to the visitor. The aesthetic experience of the garden is that of its discovery in time, through the freely chosen itinerary of the visitor. This study looks at the "spatial dialogue" formed by the physical forms of the garden and the visitor’s choices in response to the possibility of movement that these forms allow. There exists several descriptions of walks in the garden of Versailles, written during Louis XIV’s reign. The methodology consists in corroborating the physical space of the garden with the existing descriptions, in order to develop an analysis of the spatial dialogue based on contemporary philosophical and scientific theories of perception.